Espinelização em sistemas cerâmicos complexos para aplicações refratárias - Sardelli, José Alvaro Previato (2024)
Refractory bricks containing carbon and in-situ spinelization [Alumina-Magnesia-Carbon (AMC)] are broadly used in steel secondary refining ladle metallurgy. Due to the increasing demand for cleaner steels, there is a growing interest in bricks free from carbon sources and with higher performance. Unlike current material technologies, focusing on concepts of thermal shock resistance and slag resistance, bricks with engineered microstructures, carbon-free and with in-situ or pre-spinelized spinel, emerge as an alternative to meet the current demand for performance and for the low carbon steels production. The usual formulation involves the addition of electrofused alumina sources (brown or white), magnesia sources, carbon sources (graphite, pitch, carbon black, etc.), antioxidants, and a binder, typically based on resins (phenolic or novolac). As an additional contribution to literature and technology, this study proposed in three different technological approaches: i) a comparison between the most addressed aluminate formation mechanisms in the literature (MgAl2O4), compared to ZnAl2O4 formed in-situ or pre-formed added; ii) the addition of ZnO as a mineralizing agent in the Al2O3-MgO system, aiming for the anticipation of spinelization and its impact on properties at lower temperatures; iii) understanding complex spinels systems (Al2O3-MgO-ZnO) and their potential use for refractory applications. It was observed that the distinct in-situ reaction mechanisms base on the added oxides affected the physical and thermomechanical properties of high-alumina bricks, with the Kirkendall effect displaying a significant role. When evaluating the addition of MgO and ZnO in the same system for in-situ spinelization, a positive synergy was observed between the early spinelization of ZnAl2O4 and the benefits of the presence of MgAl2O4 at high temperatures. Additionally, when adding zinc in the form of pre-formed or complex spinel, considerable improvements in properties were noted, expanding, and innovating the possibilities of using ZnO in refractory ceramics.